Effect of Thai traditional play protocol on working memory and inhibitory control in children with attention-deficit/hyperactivity disorder - Chinchai, Krongporn; Sriphetcharawut, Sarinya (Journal of Associated Medical Sciences, 2021)
Background: Children with attention-deficit/hyperactivity disorder (ADHD) commonly have problems with executive functions (EFs), especially working memory and inhibitory control. There are a growing number of appropriate EF interventions for children with ADHD. Since all aspects of occupational functioning can be affected, occupational therapists have much to offer in providing interventions for school-aged children with ADHD to improve their executive function skills. Objectives: The aim of this research was to examine the effects of Thai traditional play protocol on working memory and inhibitory control in children with ADHD. Materials and methods: The study was conducted with a one group-pretest-posttest research design. Seven school-aged children with ADHD, aged between 8 and 9 years with T-scores ≥ 65 on the Behavioral Rating Inventory of Executive Function (BRIEF), Parent Form: Thai version, participated in this study. The Thai traditional play protocol was designed and developed by researchers. Twenty Thai traditional play activities that had cognitive challenges focusing on working memory and inhibitory control skills were selected and analyzed. Self-regulatory strategies, heavy work activities, and parent education were also implemented. Children with ADHD participated in a 24-session protocol, across 8 weeks with 3 sessions per week, lasting 60 minutes per session. An outcome measure was the Stroop Color and Word Test (SCWT): Children Edition. Data was analyzed using descriptive and non-parametric statistics. Results: By using the Wilcoxon Signed-Rank Test, a comparison of SCWT scores between before and after receiving a protocol showed a statistical difference of p<0.05 in working memory, whereas no statistically significant difference was found in inhibitory control (p>0.05). Conclusion: The findings demonstrated the positive effect of Thai traditional play protocol on working memory in children with ADHD. Occupational therapists can apply this protocol as a prototype for planning intervention focusing on working memory for school-aged children with ADHD.